Karl Kautsky on democracy and republicanism - Kautsky, Karl, 1854-1938 (Historical materialism book series ;, 2020)
"Once deemed 'the pope of Marxism', Karl Kautsky (1854-1938) was the leading theoretician of the German Social Democratic Party and one of the most prominent public intellectuals of his time. However, during the twentieth century a constellation of historical factors ensured that his ideas were gradually consigned to near oblivion. Not only has his political thought been dismissed in non-Marxist historical and political discourse, but his ideas are equally discredited in Marxist circles. This book aims to rekindle interest in Kautsky's ideas by exploring his democratic-republican understanding of state and society. It demonstrates how Kautsky's republican thought was positively influenced by Marx and Engels - especially in relation to the lessons they drew from the experience of the Paris Commune"--